2021
DOI: 10.1002/hon.2939
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab vedotin consolidation after autologous stem cell transplantation for Hodgkin lymphoma: A Fondazione Italiana Linfomi real‐life experience

Abstract: The standard management for relapsed or refractory classical Hodgkin lymphoma (cHL) is salvage therapy followed by autologous stem cell transplantation (ASCT). This strategy allows almost 50% of patients to be cured. Post‐ASCT maintenance treatment with brentuximab vedotin (BV) confers improved progression‐free survival (PFS) to cHL patients at high risk of relapse. We investigated the outcome of 105 cHL patients receiving post‐ASCT BV maintenance in the real‐life setting of 23 Italian hematology centers. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…A median number of 12 cycles were delivered to all patients, which is comparable to previously reported studies. 10-12 Despite 44% of patients having prior BV exposure, total mean number of BV cycles during maintenance was similar in the BV-exposed versus BV-naïve patients (10.6 vs . 11 cycles) which highlights that toxicity management and dose reductions were appropriate.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A median number of 12 cycles were delivered to all patients, which is comparable to previously reported studies. 10-12 Despite 44% of patients having prior BV exposure, total mean number of BV cycles during maintenance was similar in the BV-exposed versus BV-naïve patients (10.6 vs . 11 cycles) which highlights that toxicity management and dose reductions were appropriate.…”
Section: Discussionmentioning
confidence: 90%
“…In a study conducted in Italy, early treatment discontinuations were reported at a rate of 44%, with the most common reason for discontinuation being toxicity. 10 A real-world study assessing patients who received BV maintenance in Europe found that the median cycles of BV maintenance completed was 11. 11 A similar study from Colombia also illustrated that the median number of cycles for BV maintenance was 12 and 18% of patients had grade 3 or higher PN.…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, 75 patients were analyzed at a median follow-up of 26 months, and 50 patients had an ongoing response (CR in 41 cases), for 2-year PFS and OS rates of 68% and 88%, respectively [ 93 ]. In Italy, 105 patients with CHL (both naïve and previously exposed to BV) were analyzed at a median follow-up of 20 months, and the 3-year PFS and OS rates were 62% and 86%, respectively, once again confirming the real-life activity of BV [ 94 ]. Although most observational studies were not comparative, a retrospective comparison between BV and chemotherapy in 312 patients from the UK and Germany with a relapse after ASCT (196 treated with BV) showed a median PFS of 27 months for BV, versus 13 months for chemotherapy, with longer 1-year OS rate for BV (78% versus 66%) [ 95 ].…”
Section: Management Of Refractory and Relapsed Diseasementioning
confidence: 99%
“…Real-world data on brentuximab vedotin for cHL have demonstrated the utility and feasibility of CD30-targeted ADC therapy beyond the setting of clinical trials and specialized centers (Table 3). Although there was a paucity of data on the real-world use of brentuximab vedotin as consolidation therapy post-ASCT for some time, several recent retrospective studies have assessed the effectiveness of this approach in adults, children, and adolescents, and support the results of the AETHERA trial [50][51][52][53][54]. Real-world data also support the efficacy and acceptable safety profile of brentuximab vedotin in adults with refractory or relapsed cHL [55,56], including as a bridge to ASCT [57], and the use of brentuximab vedotin in combination with bendamustine in children, adolescents, and adults with cHL [58,59].…”
Section: Real-world Data On Brentuximab Vedotin In Chlmentioning
confidence: 99%